2013
DOI: 10.13080/z-a.2013.100.019
|View full text |Cite
|
Sign up to set email alerts
|

Responses of sunflower (Helianthus annuus L.) to irrigation and nitrogen fertilization rates

Abstract: This study was conducted to determine the effects of different nitrogen rates (0, 40, 80, 120, 160, 200 and 240 kg ha -1 N) on the yield, its components and the quality characters of sunflower (Helianthus annuus L.) and to identify the economic optimum N rate for maximum profit under both irrigated and non-irrigated conditions during a 2-year period (2007)(2008). As the N rates increased, all of the traits measured significantly increased, except the crude oil content, under both irrigation treatments. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…These results may regard to nitrogen role in activating the growth and yield components. These results are in line with that of Awed 2010 andSincik, et al (2013). They studied the effects of different nitrogen rates (0,40,80,120,160,200 and 240 kg ha -1 N) on the yield, its components and the quality characters of sunflower.…”
Section: Stem Diameter(cm) and Leaves Number Plant -1supporting
confidence: 84%
See 1 more Smart Citation
“…These results may regard to nitrogen role in activating the growth and yield components. These results are in line with that of Awed 2010 andSincik, et al (2013). They studied the effects of different nitrogen rates (0,40,80,120,160,200 and 240 kg ha -1 N) on the yield, its components and the quality characters of sunflower.…”
Section: Stem Diameter(cm) and Leaves Number Plant -1supporting
confidence: 84%
“…Agbede 2009,). On the other hand, many researchers stated that nitrogen fertilizers significantly increased sunflower plant height, dry matter, seed production, oil yield (Oyinlola et al, 2010;Sincik et al, 2013;Salih, 2013). However, other investigator found that seed oil percentage decreased with increasing nitrogen fertilizer rates (El-kady et al,2010 andAwed 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers revealed that oil yield/fad was increased by increasing nitrogen fertilization, Basha (2000), Mohamed (2003), Al-Thabet (2006), Hassan (2010), Yasein (2010) and Sincik et al, (2013).…”
Section: Resultsmentioning
confidence: 99%
“…The favorable effects of applying mineral nitrogen fertilization on growth, yield attributes, seed yield and quality of sunflower were reported by Zeiton (1992), Geweifel et al, (1997), Metwally (1997), El-Kalla et al, (1998), Abou-Khadrah et al, (2000), Basha (2000), Abd El-samie et al, (2002), Abou-Khadrah et al, (2002), Ibrahim et al, (2003), Khalil (2003), Mohamed (2003), Ali et al, (2004), Al-Thabet (2006), Ibrahim et al, (2006), El-Sarag (2007), Gholinezhad et al, (2009), Hassan (2010), Sala et al, (2010), Soleimanzadeh et al, (2010), Yasein (2010), Ali et al, (2012), Namvar et al, (2012), Wabekwa et al, (2012), Ali and Noorka (2013) and Sincik et al, (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fertilization is one of the most important crop management techniques for production of field crops (Janušauskaitė, 2013), especially in conditions affected by adverse environmental factors (Sincik et al, 2013). Nitrogen nutrition influences the plant photosynthetic capacity through the decrease of synthesis of several key photosynthetic enzymes, especially of Rubisco (ribulose-1,5-bisphosphate carboxylase/oxygenase), thus affecting the carbon assimilation, and subsequently also the photochemical processes in thylakoid membranes (Harbinson et al, 1990).…”
Section: Introductionmentioning
confidence: 99%